Changes on economic freedom in 11 post-socialist countries of Central-Eastern and South-Eastern Europe in 1996–2022 - Lach, Bartłomiej; Malaga, Krzysztof (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: One of the most important dimensions of socio-economic development in democratic countries with market economies remains economic freedom. In this context, it is worth assessing the evolution of economic freedom in 11 countries of Central and Eastern Europe and South-Eastern Europe: Bulgaria, Croatia, Czech Republic, Estonia, Hungary, Lithuania, Latvia, Poland, Romania, Slovenia, Slovakia during the period of institutional transformations in 1996–2022. Aim: The aim of the article is to present the results on correlation, s-convergence and s-divergence, as well as a multidimensional comparative analysis in the field of economic freedom. In order to conduct comparative analyzes, the economic freedom indexes published by The Heritage Foundation in Washington and Wall Street Journal will be used. They measure 12 quantitative and qualitative aspects grouped around the four pillars of economic freedom: Rule of Law — property rights, government integrity, judicial effectiveness; Government Size — government spending, tax burden, fiscal health; Efficiency regulators — business freedom, labour freedom, monetary freedom; Open Markets — trade freedom, investment freedom, financial freedom. Results: The obtained results allow us to assess the generally positive changes in economic freedom in its 12 partial and 1 general aspects in relation to each country separately, as well as in relation to the group of countries that joined the European Union after 2003. They are a significant supplement to the knowledge about creating economic freedom in 11 post-socialist countries in the years 1996–2022.